Lower health risks of potentially toxic metals after transplantation of aquacultural farmed mussels from a polluted site to unpolluted sites: a biomonitoring study in the Straits of Johore - Yap, Chee Kong; Al Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present field-based study aimed to determine the levels of six potentially toxic metals (PTM)s (Cd, Cu, Fe, Ni, Pb, and Zn determined using a flame atomic-absorption spectrophotometer) using transplanted green-lipped mussel Perna viridis from a polluted site at Kampung Pasir Puteh (KPP) to unpolluted sites at Kampung Sungai Melayu (KSM) and Sungai Belungkor (SB) in the Johore Straits (SOJ), and to estimate the human health risks of the PTMs after the depuration periods. Interestingly, after 10 weeks of depuration in the two unpolluted sites, there were 55.6–88.4% and 51.3–91.7% reductions of the six PTMs after transplantation from KPP to SB and KSM, respectively. Lower risks of health assessments were recorded and judged on the present findings of significantly (p < 0.05) lower levels of safety guidelines, significantly (p < 0.05) lower values of target hazard quotient, and significantly (p < 0.05) lower values of estimated weekly intake, of all the six PTMs after 10 weeks of depuration of the transplanted polluted mussels to the two unpolluted sites in the SOJ. Thus, further reducing the noncarcinogenic risks of the PTMs to the consumers. From an aquacultural point of view, this depuration technique can be recommended to reduce the health risks of PTMs to mussel consumers.